Inflammatory Dermatoses: The Basics - Smoller, Bruce R.; Hiatt, Kim M.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Inflammatory Dermatoses: The Basics will serve as an effective and efficient handbook for the student of dermatopathology, and as a practical bench reference for the practicing diagnostician who desires rapid access to criteria that are useful in differentiating histologically similar entities. The chapters consist of essential bullet points arranged in organized outlines allowing for easy access and direct comparison between entities. The elaborate pictorial documentation will also enable the book to serve as an atlas of the most common dermatologic disorders.
Superficial Perivascular Dermatitis -- Lichenoid/Vacuolar Dermatitis -- Superficial Perivascular Dermatitis with Spongiotic Epidermal Changes -- Superficial Perivascular Dermatitis with Psoriasiform Epidermal Changes -- Superepidermal Blistering Processes -- Intraepidermal Blisters -- Granulomatous Dermatitis -- Cutaneous Vasculitis -- Alopecias -- Panniculitis -- Histologic Mimics of Cutaneous Lymphoma -- Dermal Pigmentary Disorders -- Dermal Deposition Disorders Without Pigment.
Keywords: Medicine; Dermatology; Pathology; Medicine & Public Health; Pathology; Dermatology